Quality of life assessment in the late postoperative period of patients with rectal cancer submitted to total mesorectal excision - França Neto,Paulo Rocha (2013)
After the introduction of total mesorectal excision (TME) and radiochemotherapy, excellent results have been achieved in the treatment of patients with rectal cancer. With better oncologic control of the disease, the functional results of this type of therapeutic approach and their impact on the quality of life (QOL) of patients started to be increasingly valued. The aims of this study were to evaluate the QOL of patients with rectal cancer submitted to TME in the late postoperative period and the possible factors that directly influence their quality of life. A total of 72 patients submitted to TME due to extraperitoneal rectal tumor were assessed, after at least one postoperative year, by applying QOL questionnaires (EORTC QLQ-C30 and EORTC QLQ-CR38), in addition to a specific clinical questionnaire and rectal examination. Patients were evaluated regarding gender, age, indication of radiotherapy and chemotherapy preoperatively, length of postoperative period, distance from the anastomosis to the anal verge and general health status. The mean overall health status of patients was satisfactory (82.06). There was no difference in overall health status between patients with respect to gender, but the male patients had less insomnia (p = 0.002), better future prospects (p = 0.011), fewer effects of chemotherapy (p = 0.020) and better sexual function (p < 0.0001). Patients younger than 50 years had fewer urinary problems (p = 0.035), whereas those older than 65 years reported poorer sexual function (p = 0.012). Patients who underwent neoadjuvant therapy had more diarrhea (p = 0.012). Quality of life did not change significantly with time after surgery and the distance from the anastomosis to the anal verge. We conclude that patients undergoing TME have a good quality of life one year after the surgery and that the factors capable of affecting QOL should be identified and improved.